Time of day influences memory formation and dCREB2 proteins in Drosophila - Fropf, Robin; Zhang, Jiabin; Tanenhaus, Anne; Fropf, Whitney; Siefkes, Ellen; Yin, Jerry (Frontiers in Systems Neuroscience, 2014)
Many biological phenomena oscillate under the control of the circadian system, exhibiting peaks and troughs of activity across the day/night cycle. In most animal models, memory formation also exhibits this property, but the underlying neuronal and molecular mechanisms remain unclear. The dCREB2 transcription factor shows circadian regulated oscillations in its activity, and has been shown to be important for both circadian biology and memory formation. We show that the time-of-day (TOD) of behavioral training affects Drosophila memory formation. dCREB2 exhibits complex changes in protein levels across the daytime and nighttime, and these changes in protein abundance are likely to contribute to oscillations in dCREB2 activity and TOD effects on memory formation.